2009
DOI: 10.1371/journal.pone.0004447
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Dependent Infra-Slow (<0.1 Hz) Oscillations in Thalamic Networks

Abstract: An increasing number of EEG and resting state fMRI studies in both humans and animals indicate that spontaneous low frequency fluctuations in cerebral activity at <0.1 Hz (infra-slow oscillations, ISOs) represent a fundamental component of brain functioning, being known to correlate with faster neuronal ensemble oscillations, regulate behavioural performance and influence seizure susceptibility. Although these oscillations have been commonly indicated to involve the thalamus their basic cellular mechanisms rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 57 publications
3
103
0
Order By: Relevance
“…The monoamines (norepinephrine and serotonin) and acetylcholine each have independent modulatory effects on naturally occurring slow oscillations within the CNS (23)(24)(25)(26). During WAKE and SWS, these systems are all active to some degree, and their independent, uncoordinated effects may be reflected in the broadly asynchronous fluctuations seen during these states.…”
Section: Temporal Dynamics Of the Interactions Between Heteromodal Andmentioning
confidence: 99%
“…The monoamines (norepinephrine and serotonin) and acetylcholine each have independent modulatory effects on naturally occurring slow oscillations within the CNS (23)(24)(25)(26). During WAKE and SWS, these systems are all active to some degree, and their independent, uncoordinated effects may be reflected in the broadly asynchronous fluctuations seen during these states.…”
Section: Temporal Dynamics Of the Interactions Between Heteromodal Andmentioning
confidence: 99%
“…Recent studies report on the role of infra-slow cortical potential oscillations in the modulation of conventional frequency bands (Lörincz, Geall, Bao, Crunelli, & Hughes, 2009;van Putten et al, 2015). Therefore, modulation of these infra-slow oscillations during ILF NF sessions could exert a modulating and normalizing influence on EEG bands in depressed individuals participated in our study.…”
Section: Discussionmentioning
confidence: 94%
“…In this context, it is interesting to note that Hughes and colleagues demonstrated that infra-slow oscillations, a particular network rhythm at <0.1 Hz recorded in thalamic slices, can be induced by the application of acetylcholine and metabotropic glutamate receptor agonists, and depends on the activation of adenosine A1 receptors[112]. The adenosine modulating the infra-slow oscillations derives from the hydrolysis of ATP and activates Ba 2+ -sensitive K + channels.…”
Section: Astrocytes As Neuromodulatorsmentioning
confidence: 99%
“…The adenosine modulating the infra-slow oscillations derives from the hydrolysis of ATP and activates Ba 2+ -sensitive K + channels. Although direct experimental evidence was not provided in that study, the authors suggest that thalamic astrocytes could represent the major source of the ATP/adenosine regulating the infra-slow oscillation[112]. …”
Section: Astrocytes As Neuromodulatorsmentioning
confidence: 99%